Comparison of prostaglandin and mechanical cervical ripening in the setting of small for gestational age neonates*. (17th November 2019) - Rossi, Robert M.; Warshak, Carri R.; Masters, Heather R.; Regan, Jodi K.; Kritzer, Sara A.; Magner, Kristin P.
Abstract: Objective: The objective of this study is to determine whether cervical ripening with misoprostol (MP) is associated with higher rates of cesarean delivery (CD) compared with dinoprostone (DP) or Pitocin/Foley balloon (PFB) in infants found to be small for gestational age (SGA). Study design: Single center institution based cohort study of all inductions between 2008 and 2012 where birth weight was found to be as SGA (< 10th percentile). Maternal demographic, obstetric, and labor characteristics were compared between SGA births where cervical ripening with MP, DP, or PFB was used as the primary agent. The primary outcome was CD after attempted induction between the three study groups which included MP, DP, and PFB. Secondary outcomes included inability to achieve active labor (defined as cervical dilation of 6 cm or greater), cervical dilation at the time of CD, the incidence of CD for the indication of non-reassuring fetal status, and neonatal outcomes including Apgar scores and admission to neonatal intensive care unit. Multivariable logistic regression was performed to evaluate the association of these outcomes with MP as the induction agent versus the referent groups, PFB. Results: Of 260 inductions where the infant was found to be SGA by birth weight during the 5-year period, 172 (66.2%) patients were induced using MP, 38 (14.6%) with DP, and 50 (19.2%) with PFB. There were no differences in baseline characteristics between groups (age, race, BMI, parity, induction indication, birth weights, or maternal comorbidities). MP did not increase rate of CD which was 25.6%, 26.3%, and 22.0% in the MP, DP, and PFB groups, respectively ( p = .86). There were also no differences in incidence of CD for non-reassuring fetal well-being (NRFWB), failure to attain active labor, or cervical dilation at time of CD between induction groups. NICU admission was 18%, 18%, and 16% ( p = .94) between MP, DP, and PFB groups, respectively. MP was not associated with an increased rate of CD when compared with the other two agents combined, aOR 0.93 (0.67–1.30, 95% CI). Conclusion: MP appears to have similar efficacy and safety when compared with other cervical ripening agents in pregnancies complicated by SGA.